2021
DOI: 10.1016/j.acap.2020.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Hunger Threaten the Foundations of Child Health

Abstract: T A G G E D P ON THE FACE of it, childhood obesity and child hunger seem like very different problems. However, a deeper look reveals that the root causes of each are intertwined and overlapping. Both are conditions of poverty, both result from lack of nutritious food, and both lead to disease and affect large numbers of children. Childhood obesity and food insecurity can co-occur, and in some children food insecurity is associated with an increased risk of obesity. 1,2 Further, and especially important now, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Immigrant mothers have healthier prepregnancy weight, but this protective factor against childhood obesity is later offset by risks associated with their families' immigrant status-for example, food insecurity, which is associated with obesity and has been linked to exclusion from nutrition assistance programs. 22,23 'Illegality' As A Social Determinant Of Health…”
Section: Immigrant Status As a Social Determinant Of Healthmentioning
confidence: 99%
“…Immigrant mothers have healthier prepregnancy weight, but this protective factor against childhood obesity is later offset by risks associated with their families' immigrant status-for example, food insecurity, which is associated with obesity and has been linked to exclusion from nutrition assistance programs. 22,23 'Illegality' As A Social Determinant Of Health…”
Section: Immigrant Status As a Social Determinant Of Healthmentioning
confidence: 99%
“…Although our previous study showed that completing the PALS by itself was feasible in a clinical setting [ 29 , 30 , 35 ], the present study and online platform did not differentiate the time of completion of the PALS from that of responding to the messages, the message evaluation, and user acceptability ratings as well as activities that may not be needed in clinical practice (e.g., time required for the consenting process, metadata collection). This study also showed that family food insecurity can be discreetly assessed via online screening—followed by emailing community resources to families directly—to minimize stigma [ 25 ] and support improved food access for obesity prevention and health [ 73 ].…”
Section: Discussionmentioning
confidence: 99%